Intramolecular glycosylation - Jia, Xiao G.; Demchenko, Alexei V. (Beilstein Journal of Organic Chemistry, 2017)
Carbohydrate oligomers remain challenging targets for chemists due to the requirement for elaborate protecting and leaving group manipulations, functionalization, tedious purification, and sophisticated characterization. Achieving high stereocontrol in glycosylation reactions is arguably the major hurdle that chemists experience. This review article overviews methods for intramolecular glycosylation reactions wherein the facial stereoselectivity is achieved by tethering of the glycosyl donor and acceptor counterparts.
Keywords: carbohydrates; glycosylation; intramolecular reactions; oligosaccharides

(untitled) - Cummings, R. D.; Pierce, J. M. (Chem. Biol., 2014)

(untitled) - Russo, L.; Cipolla, L. (Chem. – Eur. J., 2016)

Essentials of Glycobiology - Varki, A.; Cummings, R. D.; Esko, J. D.; Freeze, H. H.; Bertozzi, C. R.; Stanley, P.; Hart, G. W.; Etzler, M. E. (CSH Laboratory Press, 2009)

(untitled) - Alonzi, D. S.; Neville, D. C. A.; Lachmann, R. H.; Dwek, R. A.; Butters, T. D. (Biochem. J., 2008)

(untitled) - Lebrilla, C. B.; An, H. J. (Mol. BioSyst., 2009)

(untitled) - Adamczyk, B.; Tharmalingam, T.; Rudd, P. M. (Biochim. Biophys. Acta, 2012)

(untitled) - Chaubard, J.-L.; Krishnamurthy, C.; Yi, W.; Smith, D. F.; Hsieh-Wilson, L. C. (J. Am. Chem. Soc., 2012)

(untitled) - Fujitani, N.; Furukawa, J.-i.; Araki, K.; Fujioka, T.; Takegawa, Y.; Piao, J.; Nishioka, T.; Tamura, T.; Nikaido, T.; Ito, M.; Nakamura, Y.; Shinohara, Y. (Proc. Natl. Acad. Sci. U. S. A., 2013)

(untitled) - Ruhaak, L. R.; Miyamoto, S.; Lebrilla, C. B. (Mol. Cell. Proteomics, 2013)

(untitled) - Zhu, X.; Schmidt, R. R. (Angew. Chem., Int. Ed., 2009)

(untitled) - McKay, M. J.; Nguyen, H. M. (ACS Catal., 2012)

(untitled) - Nigudkar, S. S.; Demchenko, A. V. (Chem. Sci., 2015)

(untitled) - Das, R.; Mukhopadhyay, B. (ChemistryOpen, 2016)

(untitled) - Li, X.; Zhu, J. (Eur. J. Org. Chem., 2016)

(untitled) - Boons, G.-J. (Tetrahedron, 1996)

Bioorganic Chemistry: Carbohydrates - Fraser-Reid, B.; Madsen, R.; Campbell, A. S.; Roberts, C. S.; Merritt, R. J. (Oxford University Press, 1999)

(untitled) - Davis, B. G. (J. Chem. Soc., Perkin Trans. 1, 2000)

(untitled) - Seeberger, P. H.; Haase, W.-C. (Chem. Rev., 2000)

(untitled) - Tanaka, H.; Yamada, H.; Takahashi, T. (Trends Glycosci. Glycotechnol., 2007)

(untitled) - Seeberger, P. H. (Chem. Soc. Rev., 2008)

(untitled) - Boltje, T. J.; Buskas, T.; Boons, G.-J. (Nat. Chem., 2009)

Progress in the synthesis of complex carbohydrate chains of plant and microbial polysaccharides - Parameswar, A. R.; Demchenko, A. V. (Transworld Res. Network, 2009)

(untitled) - Smoot, J. T.; Demchenko, A. V. (Adv. Carbohydr. Chem. Biochem., 2009)

Topics in current chemistry - Fraser-Reid, B.; López, J. C. (Springer-Verlag, 2011)

(untitled) - Kaeothip, S.; Demchenko, A. V. (Carbohydr. Res., 2011)

Solid-Phase Organic Synthesis - Tanaka, K.; Fukase, K. (John Wiley & Sons, Inc., 2012)

(untitled) - Crotti, S.; Adamo, R. (Curr. Org. Synth., 2013)

(untitled) - Yang, L.; Qin, Q.; Ye, X.-S. (Asian J. Org. Chem., 2013)

(untitled) - Yasomanee, J. P.; Demchenko, A. V. (Trends Glycosci. Glycotechnol., 2013)

(untitled) - Bennett, C. S. (Org. Biomol. Chem., 2014)

(untitled) - Bouhall, S. K.; Sucheck, S. J. (J. Carbohydr. Chem., 2014)

Carbohydrate Chemistry: State-of-the-art and challenges for drug development - Pistorio, S. G.; Stine, K. J.; Demchenko, A. V. (Imperial College Press, 2016)

(untitled) - Muthana, S.; Cao, H.; Chen, X. (Curr. Opin. Chem. Biol., 2009)

(untitled) - Mydock, L. K.; Demchenko, A. V. (Org. Biomol. Chem., 2010)

(untitled) - Crich, D. (Acc. Chem. Res., 2010)

(untitled) - Frihed, T. G.; Bols, M.; Pedersen, C. M. (Chem. Rev., 2015)

(untitled) - Bohé, L.; Crich, D. (Carbohydr. Res., 2015)

(untitled) - Jung, K.-H.; Müller, M.; Schmidt, R. R. (Chem. Rev., 2000)

Carbohydrates in Chemistry and Biology - Madsen, J.; Bols, M. (Wiley-VCH, 2000)

Handbook of Chemical Glycosylation - Ziegler, T. (Wiley-VCH Verlag GmbH & Co, 2008)

(untitled) - Ishiwata, A.; Lee, Y. J.; Ito, Y. (Org. Biomol. Chem., 2010)

(untitled) - Höök, J. E.; Lindberg, B. (Acta Chem. Scand., 1968)

(untitled) - Malysheva, N. N.; Torgov, V. I.; Klimov, E. M.; Kochetkov, N. K. (Izv. Akad. Nauk SSSR, Ser. Khim., 1974)

(untitled) - Inaba, S.; Yamada, M.; Yoshino, T.; Ishido, Y. (J. Am. Chem. Soc., 1973)

(untitled) - Barresi, F.; Hindsgaul, O. (J. Am. Chem. Soc., 1991)

(untitled) - Kusumoto, S.; Imoto, M.; Ogiku, T.; Shiba, T. (Bull. Chem. Soc. Jpn., 1986)

(untitled) - Jia, X. G. (University of Missouri, 2016)

(untitled) - Fairbanks, A. J. (Synlett, 2003)

(untitled) - Cumpstey, I. (Carbohydr. Res., 2008)

(untitled) - Bols, M.; Skrydstrup, T. (Chem. Rev., 1995)

(untitled) - Wakao, M.; Fukase, K.; Kusumoto, S. (J. Org. Chem., 2002)

(untitled) - Ziegler, T.; Lau, R. (Tetrahedron Lett., 1995)

(untitled) - Lau, R.; Schüle, G.; Schwanaberg, U.; Ziegler, T. (Liebigs Ann., 1995)

(untitled) - Valverde, S.; Gómez, A. M.; Hernández, A.; Herradón, B.; López, J. C. (J. Chem. Soc., Chem. Commun., 1995)

(untitled) - Yamada, H.; Imamura, K.; Takahashi, T. (Tetrahedron Lett., 1997)

(untitled) - Pornsuriyasak, P.; Jia, X. G.; Kaeothip, S.; Demchenko, A. V. (Org. Lett., 2016)

(untitled) - Lemanski, G.; Ziegler, T. (Tetrahedron, 2000)

(untitled) - Lemanski, G.; Ziegler, T. (Helv. Chim. Acta, 2000)

(untitled) - Wakao, M.; Fukase, K.; Kusumoto, S. (Synlett, 1999)

(untitled) - Ziegler, T.; Ritter, A.; Hürttlen, J. (Tetrahedron Lett., 1997)

(untitled) - Ziegler, T.; Lemanski, G. (Eur. J. Org. Chem., 1998)

(untitled) - Ziegler, T.; Lemanski, G.; Hürttlen, J. (Tetrahedron Lett., 2001)

(untitled) - Claude, P.; Lehmann, C.; Ziegler, T. (Beilstein J. Org. Chem., 2011)

(untitled) - Valverde, S.; Gómez, A. M.; López, J. C.; Herradón, B. (Tetrahedron Lett., 1996)

(untitled) - Valverde, S.; García, M.; Gómez, A. M.; López, J. C. (Synlett, 2000)

(untitled) - Valverde, S.; García, M.; Gómez, A. M.; López, J. C. (Chem. Commun., 2000)

(untitled) - Cid, M. B.; Valverde, S.; López, J. C.; Gómez, A. M. (Synlett, 2005)

(untitled) - Huchel, U.; Schmidt, R. R. (Tetrahedron Lett., 1998)

(untitled) - Müller, M.; Huchel, U.; Geyer, A.; Schmidt, R. R. (J. Org. Chem., 1999)

(untitled) - Müller, M.; Schmidt, R. R. (Eur. J. Org. Chem., 2001)

(untitled) - Abdel-Rahman, A. A.-H.; El Ashry, E. S. H.; Schmidt, R. R. (Carbohydr. Res., 2002)

(untitled) - Paul, S.; Müller, M.; Schmidt, R. R. (Eur. J. Org. Chem., 2003)

(untitled) - Schüle, G.; Ziegler, T. (Tetrahedron, 1996)

(untitled) - Lemanski, G.; Ziegler, T. (Eur. J. Org. Chem., 2006)

(untitled) - Ogawa, T.; Takahashi, Y. (Carbohydr. Res., 1985)

(untitled) - Tennant-Eyles, R. J.; Fairbanks, A. J.; Davis, B. G. (Chem. Commun., 1999)

(untitled) - Tennant-Eyles, R. J.; Davis, B. G.; Fairbanks, A. J. (Tetrahedron: Asymmetry, 2000)

(untitled) - Tennant-Eyles, R. J.; Davis, B. G.; Fairbanks, A. J. (Tetrahedron: Asymmetry, 2003)

(untitled) - Greenwell, D. R.; Ibnouzaki, A. F.; Warriner, S. L. (Angew. Chem., Int. Ed., 2002)

(untitled) - Tiwari, V. K.; Kumar, A.; Schmidt, R. R. (Eur. J. Org. Chem., 2012)

(untitled) - Kumar, A.; Geng, Y.; Schmidt, R. R. (Eur. J. Org. Chem., 2012)

(untitled) - Jia, X. G.; Pornsuriyasak, P.; Demchenko, A. V. (J. Org. Chem., 2016)

(untitled) - Barresi, F.; Hindsgaul, O. (Can. J. Chem., 1994)

(untitled) - Stork, G.; Kim, G. (J. Am. Chem. Soc., 1992)

(untitled) - Bols, M. (J. Chem. Soc., Chem. Commun., 1992)

(untitled) - Bols, M. (Acta Chem. Scand., 1993)

(untitled) - Bols, M. (J. Chem. Soc., Chem. Commun., 1993)

(untitled) - Bols, M. (Tetrahedron, 1993)

(untitled) - Bols, M.; Hansen, H. C. (Chem. Lett., 1994)

(untitled) - Buchan, Z. A.; Bader, S. J.; Montgomery, J. (Angew. Chem., Int. Ed., 2009)

(untitled) - Walk, J. T.; Buchan, Z. A.; Montgomery, J. (Chem. Sci., 2015)

(untitled) - Seward, C. M. P.; Cumpstey, I.; Aloui, M.; Ennis, S. C.; Redgrave, A. J.; Fairbanks, A. J. (Chem. Commun., 2000)

(untitled) - Cumpstey, I.; Fairbanks, A. J.; Redgrave, A. J. (Org. Lett., 2001)

(untitled) - Ito, Y.; Ogawa, T. (Angew. Chem., Int. Ed. Engl., 1994)

(untitled) - Dan, A.; Ito, Y.; Ogawa, T. (J. Org. Chem., 1995)

(untitled) - Dan, A.; Lergenmüller, M.; Amano, M.; Nakahara, Y.; Ogawa, T.; Ito, Y. (Chem. – Eur. J., 1998)

(untitled) - Ito, Y.; Ogawa, T. (J. Am. Chem. Soc., 1997)

(untitled) - Pratt, M. R.; Leigh, C. D.; Bertozzi, C. R. (Org. Lett., 2003)

(untitled) - Leigh, C. D.; Bertozzi, C. R. (J. Org. Chem., 2008)

(untitled) - Ishiwata, A.; Munemura, Y.; Ito, Y. (Eur. J. Org. Chem., 2008)

(untitled) - Yong, J. L.; Ishiwata, A.; Ito, Y. (J. Am. Chem. Soc., 2008)

(untitled) - Ishiwata, A.; Ito, Y. (Trends Glycosci. Glycotechnol., 2009)

(untitled) - Ishiwata, A.; Kaeothip, S.; Takeda, Y.; Ito, Y. (Angew. Chem., Int. Ed., 2014)

(untitled) - Ishiwata, A.; Ito, Y. (J. Am. Chem. Soc., 2011)

(untitled) - Ishiwata, A.; Sakurai, A.; Nishimiya, Y.; Tsuda, S.; Ito, Y. (J. Am. Chem. Soc., 2011)

(untitled) - Ishiwata, A.; Ito, Y. (Yuki Gosei Kagaku Kyokaishi, 2012)

(untitled) - Kaeothip, S.; Ishiwata, A.; Ito, Y. (Org. Biomol. Chem., 2013)

Glycochemical Synthesis: Strategies and Applications - Ishiwata, A.; Ito, Y. (John Wiley & Sons, 2015)

(untitled) - Nakagawa, A.; Tanaka, M.; Hanamura, S.; Takahashi, D.; Toshima, K. (Angew. Chem., Int. Ed., 2015)

(untitled) - Tanaka, M.; Nashida, J.; Takahashi, D.; Toshima, K. (Org. Lett., 2016)

(untitled) - Nishi, N.; Nashida, J.; Kaji, E.; Takahashi, D.; Toshima, K. (Chem. Commun., 2017)

(untitled) - Smoot, J. T.; Pornsuriyasak, P.; Demchenko, A. V. (Angew. Chem., Int. Ed., 2005)

(untitled) - Smoot, J. T.; Demchenko, A. V. (J. Org. Chem., 2008)

(untitled) - Yasomanee, J. P.; Demchenko, A. V. (J. Am. Chem. Soc., 2012)

(untitled) - Yasomanee, J. P.; Demchenko, A. V. (Chem. – Eur. J., 2015)

(untitled) - Yasomanee, J. P.; Demchenko, A. V. (Angew. Chem., Int. Ed., 2014)

(untitled) - Pistorio, S. G.; Yasomanee, J. P.; Demchenko, A. V. (Org. Lett., 2014)

(untitled) - Yasomanee, J. P.; Parameswar, A. R.; Pornsuriyasak, P.; Rath, N. P.; Demchenko, A. V. (Org. Biomol. Chem., 2016)

(untitled) - Kayastha, A. K.; Jia, X. G.; Yasomanee, J. P.; Demchenko, A. V. (Org. Lett., 2015)

(untitled) - Xiang, S.; He, J.; Tan, Y. J.; Liu, X.-W. (J. Org. Chem., 2014)

(untitled) - Xiang, S.; Hoang, K. L. M.; He, J.; Tan, Y. J.; Liu, X.-W. (Angew. Chem., Int. Ed., 2015)

(untitled) - Behrendt, M. E.; Schmidt, R. R. (Tetrahedron Lett., 1993)

(untitled) - Scheffler, G.; Schmidt, R. R. (Tetrahedron Lett., 1997)

(untitled) - Scheffler, G.; Behrendt, M. E.; Schmidt, R. R. (Eur. J. Org. Chem., 2000)

(untitled) - Azumaya, I.; Kotani, M.; Ikegami, S. (Synlett, 2004)

(untitled) - Azumaya, I.; Niwa, T.; Kotani, M.; Iimori, T.; Ikegami, S. (Tetrahedron Lett., 1999)

(untitled) - Scheffler, G.; Schmidt, R. R. (J. Org. Chem., 1999)

(untitled) - Laursen, J. B.; Petersen, L.; Jensen, K. J. (Org. Lett., 2001)

(untitled) - Liu, X.; Zhang, B.; Gu, X.; Chen, G.; Chen, L.; Wang, X.; Xiong, B.; You, Q.-D.; Chen, Y.-L.; Shen, J. (Carbohydr. Res., 2014)